Fibrinogen gamma gene rs2066865 and risk of cancer-related venous thromboembolism - Paulsen, Benedikte (UiT Norges arktiske universitet, 2019)
Venous thromboembolism is a frequent complication in patients with cancer. Homozygous carriers of the fibrinogen gamma gene (FGG) rs2066865 have a moderately increased risk of venous thromboembolism, but the effect of the FGG variant in cancer is unknown. We aimed to investigate the effect of the FGG variant and active cancer on the risk of venous thromboembolism. Cases with incident venous thromboembolism (n= 640) and a randomly selected age-weighted sub-cohort (n=3734) were derived from a population-based cohort (the Tromsø study). Cox-regression was used to estimate hazard ratios with 95% confidence intervals for VTE according to categories of cancer and FGG. In those without cancer, homozygosity at the FGG variant was associated with a 70% (HR 1.7 95% CI 1.2-2.3) increased risk of venous thromboembolism compared to non-carriers. Cancer patients homozygous for the FGG variant had a 2-fold (HR 2.0 95% CI 1.1-3.6) higher risk of venous thromboembolism than cancer patients without the variant. Moreover, the 6-month cumulative incidence of venous thromboembolism among cancer patients was 6.4% (95% CI, 3.5%-11.6%) in homozygous carriers of FGG and 3.1% (95% CI, 2.3%-4.7%) in those without risk alleles. A synergistic effect was observed between rs2066865 and active cancer on the risk of VTE (Synergy index: 1.81, 95% CI: 1.02-3.21, Attributable proportion: 0.43, 95% CI: 0.11-0.74). In conclusion, homozygosity at the FGG variant and active cancer yielded synergistic effect on the risk of venous thromboembolism.